"Clinical comparison of bond failure rate between two types of mandibular canine-canine bonded orthodontic retainers- a randomized clinical trial" - Nasreen Iqbal Nagani; Imtiaz Ahmed; Faiqa Tanveer; Hafiza Marium Khursheed; Waqas Ahmed Farooqui (BMC, 2020)
Abstract Background Bonded retainers are widely used as they are esthetically pleasing, easily acceptable, provide greater stability, compliance free and causes no soft tissue irritation and speech problems. Though, fracture and bond failure are their shortcomings. Therefore, the objectives of this study were to evaluate the number of bond failures and type of failure pattern between two types of mandibular canine-canine bonded retainers. Methods Total 60 subjects were recruited initially and were assessed for eligibility, out of which 6 were excluded and 2 were lost to follow up. They were randomly divided into two groups. Fiber reinforced composite (FRC) retainers were inserted in group 1 subjects while group 2 subjects received multistranded stainless steel (MSW) retainers. The subjects were recalled after every 3 months over a period of 1 year. Bond failure rate and failure pattern based on adhesive remnant index were evaluated at each visit. The bond failure rate and failure pattern were compared between the two retainers by using Chi-square test. Results The bond failure rates were 42.94% for FRC retainer and 31.41% for MSW retainer. Hence, total number of bond failures in both retainers were 37.17%. The difference of bond failure between two groups was statistically significant (p = 0.012). Type "0" failure pattern was detected commonly with both types of retainers (p <  0.001). Conclusion Our findings indicate that multistranded stainless steel wire retainer is a superior option to be used for fixed lingual retention in mandibular arch as it exhibited lower bond failure as compared to fiber reinforced composite retainer. Adhesive failure is the most common type of bond failure observed with both types of fixed retainers. Trial registration ID NCT03881813 ( https://clinicaltrials.gov/ ); March 19, 2019, retrospective registration.